2014
DOI: 10.1155/2014/268796
|View full text |Cite
|
Sign up to set email alerts
|

Ganglion Cell Complex Evaluation in Exudative Age-Related Macular Degeneration after Repeated Intravitreal Injections of Ranibizumab

Abstract: Purpose. To detect the effects of intravitreal ranibizumab injections on GCC in patients with wet AMD.Methods. 32 wet AMD eyes were selected and submitted at three ranibizumab injections. RTVue-OCT GCC and MM5 protocol were performed before treatment and twenty days after each injection.Results. At baseline mean GCC thickness was 93.9 ± 18.5 μm. Twenty days after each intravitreal injection it was, respectively, 85.8 ± 10.1, 86.5 ± 9.3, and 91.1 ± 11.5 μm, without statistical significance. A significant improv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 26 publications
0
5
0
Order By: Relevance
“…There is only one study in the literature that has looked at the short term results (after 3 intravitreal injections of ranibizumab administered monthly) of anti-VEGF therapy in humans. In that study the authors emphasized a reduction of GCC thickness but this was not statistically significant [19]. We attribute this finding to the short follow-up time in that study.…”
Section: Discussionmentioning
confidence: 63%
See 1 more Smart Citation
“…There is only one study in the literature that has looked at the short term results (after 3 intravitreal injections of ranibizumab administered monthly) of anti-VEGF therapy in humans. In that study the authors emphasized a reduction of GCC thickness but this was not statistically significant [19]. We attribute this finding to the short follow-up time in that study.…”
Section: Discussionmentioning
confidence: 63%
“…A great number of studies investigated the association between anti-VEGF treatment and RPE-choroidal atrophy by using fundus autofluorescence (FAF) or near-infrared autofluorescence, fluorescein angiogram and/or optical coherence tomography (OCT) imagings [6,[9][10][11][12][13][14][15][16]. However, there is limited study in the literature looking at the difference in retinal layers thicknesses in neovascular and nonneovascular AMD patients in order to determine the plausible effect of anti-VEGF treatment [17][18][19]. Unfortunately, all of these studies have investigated the short term effect of anti-VEGF theraphy.…”
Section: Introductionmentioning
confidence: 99%
“…Perdicchi et al studied changes in ganglion cell complex changes after treatment of age related macular degeneration with intravitreal ranibizumab. 17 Their study showed an average of 8.1 ±20.2 m after a single injection of intravitreal ranibizumab. This decrease in retinal ganglion cell complex thickness was statistically significant, although the visual acuity and central macular thickness were reduced.…”
Section: Discussionmentioning
confidence: 94%
“…17 On the other hand, certain findings showed that the GCL-IPL decrease was not significant. 18,19,31 The objective of the present study was to elucidate the relationship between anti-VEGF injections and GCL-IPL thinning using longer follow-up and a larger sample size.…”
Section: Discussionmentioning
confidence: 99%
“…9 Other reports, however, including a meta-analysis, did not confirm these observations. 10 -12 Similarly, certain studies raised the concern that the ganglion cell layer–inner plexiform layer (GCL-IPL) is another aspect of the eye that might be affected in nAMD, 13 -17 although this remains unconfirmed 18,19 (Table 1). The goal of the present study was to assess GCL-IPL thickness changes in patients with unilateral nAMD treated with intravitreal anti-VEGF injections.…”
Section: Introductionmentioning
confidence: 99%